민영의료보험 보유자의 의료서비스 이용행태 분석 - 윤성주(Sung-Joo Yoon) (재정학연구, 2019)
본 연구는 개인들의 민영의료보험 보유가 의료서비스 이용에 미치는 영향에 대해 실증분석을 통해 살펴보고, 이에 근거하여 정부의 건강보험 보장성 확대정책과 관련한 정책적 시사점을 제시하는 것을 연구의 목적으로 하고 있다. 이를 위해 한국의료패널 2008〜2014년 자료를 이용하였으며, 보이지 않는 개인의 이질성으로 인해 초래되는 내생성을 완화시키기 위해 조건부 상관임의효과모형을 이용하였다. 또한 표본분석과 더불어 연령, 소득, 의료서비스 이용수준 등을 고려하여 부표본을 구성․분석함으로써 정부가 계획․운용하고 있는 건강보험 보장성 확대정책과 관련한 시사점을 모색하고 있다. 본 연구의 실증분석 결과는 정부가 건강보험 보장성을 확대하는 데 있어 고령층과 저소득층, 그리고 중증질환자를 우선적으로 고려해야 한다는 정책적 타당성을 뒷받침하고 있으며, 의료서비스 이용에 따른 본인부담금 차등화에 대한 검토의 필요성 또한 제기하고 있다. This study examines the association between private health insurance and medical care utilization using Korea Health Panel from 2008 to 2014. For the empirical analysis, it employs correlated random effects model, which have not been applied in the related-previous studies, to mitigate the size of endogeneity that is challenging issue in health studies. Along with sample study, this study additionally investigates several subsample analyses considering age, income, medical consumption. The results support the idea that the expansion of coverage by National Health Service need to prioritize patients with serious diseases, old people, and low-income group. Also, it provides the need of differentiating deductible by the amount of medical service usage. KCI Citation Count: 0